Inovasi Baik yang Dilakukan Batik Komar terhadap Branding Batik Komar - Anjarani, Clarina Meisya (Moda : The Fashion Journal, 2024)
The importance of building a brand or brand as brand equity for a company has become the focus for achieving long-term competitive advantage. In a competitive global context, innovation is the key for companies to create new ideas, new products and improve business conditions. This research focuses on Batik Komar, a batik manufacturer that has made various innovations in its product design. The purpose of this research is to identify the branding strategies used by Batik Komar, explore the product innovations they have implemented, and analyze their impact on sales and company existence. Three research questions were asked to achieve this goal. Through this research, it is hoped that it can provide insight into the importance of innovation in the context of branding to strengthen a company’s position in the market.